PROPERTIES OF CA2+-DEPENDENT AND CA2+-INDEPENDENT ISOFORMS OF NO-SYNTHASE IN BLOOD LYMPHOCYTES OF OVARIAN CANCER WOMEN - Baryliak, R.V.; Vorobets, D.Z.; Melnyk, O.V.; Fafula, R.V.; Vorobets, Z.D. (World of Medicine and Biology, 2021)
The purpose of the present work was to study the enzyme activity and kinetic properties of NO-synthase in blood lymphocytes of women with ovarian cancer. Studies were conducted on the blood lymphocytes of women with ovarian cancer of the II-ІV degrees (n=26) and healthy women (n=24, control group). It has been found that constitutive isoform of NO-synthase of blood lymphocytes of women with ovarian cancer was 4.0 fold lower compared to control group. The activity of inducible NO-synthase in blood lymphocytes of practically healthy women was (1.52±0.46) nmol NADPH(H+)/min∙mg of protein and in women with ovarian cancer it increased in 144 times. The maximum rate of constitutive isoform of NO-synthase reaction in patients with ovarian cancer was reduced 5 fold and for inducible NO-synthase reaction was increased in tens of times compared to control group. For oncopathology the imaginary affinity constant to arginine for inducible NO-synthase was in 5.4 times lower compared to inducible NO-synthase of control group. The inhibition of constitutive isoform of NO-synthase occurs by competitive type – by reducing the rate of enzyme reaction.
Keywords: ovarian cancer; lymphocytes; Nitrogen (II) oxide; NO-synthase; arginase